Вали — важлива складова частина дерев’яно-земляних споруд укріплених поселень Х—ХІV ст. Північної Буковини - Возний, Ігор (Археологія і давня історія України., 2022)
I. P. Vozny Ramparts as the Important Component of the WoodenEarth Constructions of Fortified Settlements of the 10th—14th Centuries in the Northern Bukovyna The ramparts which were one of the important elements of defensive structures of fortified settlement structures of the 10th — first half of the 14th centuries within the northern part of Bukovyna are examined in the paper based on the analysis of archaeological material and written sources. Structural components of ramparts, their additional internal and superstructures are analyzed. Ramparts began to be actively used in the organization of defense structures of the territory under study from the turn of the 10th to the 11th centuries. The ramparts, which served as platforms for defensive log cabins, to prevent their creeping and to give them greater steepness were strengthened by additional internal rampart structures, such as a wooden wall up to 1 m high, stone crepitations, the remains of earlier fortifications of the Slavic or Early Iron age. The horizontal pad (so called berma) could be used as a means of restraining the shifting of slopes. Log cabins of various designs could be located on the ramparts or on the inner side of the fortified square. Depending on the location of the cabins in the defense system, a battle march for warriors laid out with stone slabs could be arranged on their log cover. As a rule, the battle march was covered from the outside with a wooden parapet, which was called a «zaborolo». Depending on the rank of the fortified point on which the cages were located, they could be used as combat cells from which they fired at the enemy or as household or residential rooms. In addition to log cages, in the military and defense architecture of the region wood and earth fortifications of the pillar structure were also used during the construction of the main defense line. In the second half of the 13th — 14th centuries in the ramparts of the main fortified lines of some hillforts the additional constructions began to be used — «horodni» which were absent in the hillforts of the territory under study in the 12th — the first half of the 13th century. Ramparts without internal constructions were mainly a component of additional fortified lines. Sometimes their surface could be strengthened with a stone facing. The study of ramparts on the territory of northern part of Bukovyna permits us to conclude that there is no significant difference in the equipment of similar structures in other areas of Old Rus. The involvement of significant comparative material showed that the military and defense architecture of the local population developed following the traditions of earlier epochs. At the same time by using individual local elements it is close to the military engineering art of the Old Rus and Western Europe.
Keywords: wall; horodnja; crepida; defensive cage; zaborolo; palisade